2011
DOI: 10.1097/olq.0b013e3181f41dc0
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Repeat Syphilis Testing at a Large Urban LGBT Health Clinic: Chicago, IL 2002–2008

Abstract: Timely follow-up and rescreening improved during the study period, subsequent to implementation of electronic medical records and enhanced DIS follow-up. Even in this later period, the combination of lack of timely follow-up and rescreening resulted in 39% of patients without CDC recommended follow-up. Further efforts are needed to improve timely follow-up by patients and rescreening by clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…(27) However, a recent study has shown that syphilis retesting rates in gay men in Australia are still lower than recommended. (20) Reminders to clinicians and patients have been shown to be effective at increasing STI retesting rates (28)(29) and their more widespread use should be encouraged. Contact tracing was also explored in the NGMSAP and although it was acceptable, the high level needed to impact the epidemic was unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…(27) However, a recent study has shown that syphilis retesting rates in gay men in Australia are still lower than recommended. (20) Reminders to clinicians and patients have been shown to be effective at increasing STI retesting rates (28)(29) and their more widespread use should be encouraged. Contact tracing was also explored in the NGMSAP and although it was acceptable, the high level needed to impact the epidemic was unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…In MSM irrespective of HIV status, interventions that were highly effective while low cost incorporated text message and e-mail reminders for patients to repeat STI testing at 3 to 6 month intervals [43,44], Moderately effective, low cost interventions in MSM included the adoption of updated national guidelines into clinic practice [38], EHR reminders for providers to test for syphilis and to follow-up with serologic testing after syphilis treatment [40,41], and EHR alerts to inform providers about recommendations to screen at extragenital sites [42]. Incorporating a sexual health practice nurse in the clinic was found to be moderately effective, but costly [39].…”
Section: Interventions To Improve Hiv Care-based Sti Screeningmentioning
confidence: 99%
“…Significant increases in screening rates for gonorrhoea and chlamydia (OR 1.4–1.9) have been demonstrated in observational studies using several different strategies: use of a computer alert on an electronic medical record, 10 introduction of clinic guidelines on STI screening 11 and short text messaging reminders for repeat STI screening. 12 13 Increases in syphilis testing (OR 2.3–21.4) were found using the following strategies: advocating regular serological screening for syphilis during routine HIV care 14 ; including syphilis serology testing routinely with blood tests performed as part of HIV monitoring 15 ; use of a computer alert on an electronic medical record 16 ; and an electronic medical record system with a reminder to clinicians to enhance syphilis re-testing following syphilis treatment. 17 A before and after study in Australia using existing clinical and behavioural data of clients attending a major sexual health clinic (SHC) found that an automated, computer generated text message service (SMS), providing 3 monthly reminders, doubled the testing rate for HIV, syphilis, gonorrhoea and chlamydia among MSM.…”
Section: Introductionmentioning
confidence: 99%